Transformational leadership pactices and relationship to organisational performance among administrators at IIUM - Tamimi, Alaa (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This study aims at looking into the relationship between transformational leadership and the organisational performance within International Islamic University Malaysia (IIUM). In addition, it also aims at measuring the practices of transformational leadership in IIUM. The study was carried out among 150 randomly selected administrators (63 male and 87 female) where they were asked to fill out two instruments developed by the researcher. The first of the instruments was the MLQ test which measures the practice of transformational leadership among administrators of IIUM. The other instrument was a questionnaire adopted from previous studies to identify the practices of organisational performance at IIUM. The findings show that there is a significant relationship between transformational leadership and the organisational performance at international Islamic University Malaysia. The study suggests that individualised consideration is the most practiced component of transformational leadership. Also, this study proposes that intellectual stimulation has the highest score among the relationships with organisational performance of the university. The overall results of this study shows that transformational leadership is beneficial for the educational sector.